Coating pigment
By forming a magnetite layer with a specific lattice constant on the light-transmissive material substrate and adding a protective layer, the problem of insufficient pigment color and tone performance in the prior art is solved, and high color and color development of various interference colors are achieved. Sexual effect.
Patent Information
- Application Number
- CN202180049840.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-07-14
- Filing Date
- 2021-07-07
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2041-07-07
AI Technical Summary
The prior art is difficult to provide pigments of various tones of high color, especially pigments of red, blue, yellow and green, with limited performance.
By forming a magnetite layer with a specific lattice constant on a substrate composed of a light-transmissive material, and combining protective layers such as metal oxides, metal hydroxides or resins, the thickness and crystal structure of the magnetite layer are controlled to achieve a variety of conditions. The manifestation of interference color.
The coated pigment with high color and color rendering is achieved, and can express a variety of interference colors such as red, blue, yellow to green, and significantly improve the color and color rendering of the pigment.
Smart Images

Figure CN115916910B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to coated pigments coated with a magnetite layer. Background Art
[0002] Conventionally, pigments that impart interference colors by forming a single or composite film composed of silicon oxide, titanium oxide, iron oxide, metal, or the like on the surface of a transparent substrate such as mica, alumina, or glass, or an aluminum pigment are known.
[0003] For example, Patent Document 1 discloses a coated pigment in which a ferrite layer is formed on the surface of a light-transmitting substrate or a metal substrate having a light-transmitting layer formed on the surface.
[0004] Patent Document 2 discloses an orange pearlescent pigment in which a metal oxide containing iron oxide is coated on the surface of a flaky substrate.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application Laid-Open No. 2015-178556
[0008] Patent Document 2: Japanese Patent Application Laid-Open No. 10-259318 Summary of the invention
[0009] However, the pigment of Patent Document 1 can hardly be said to have sufficient chroma and color rendering properties, and the pigment of Document 2 can only obtain red or yellow hues.
[0010] Therefore, an object of the present invention is to provide a pigment having interference colors of various hues with high chroma.
[0011] In view of the above situation, the present inventors conducted intensive studies and found that the above problems can be solved by coating a substrate having at least a surface made of a light-transmitting material with a magnetite layer and controlling the magnetite layer to have a predetermined crystal structure, thereby completing the present invention.
[0012] That is, the gist of the present invention lies in the following [1] to [8].
[0013] [1] A coated pigment comprising a substrate having at least a surface made of a light-transmitting material and a magnetite layer covering the substrate, wherein the lattice constant of the magnetite layer is above.
[0014] [2] The coated pigment according to [1], wherein the light-transmitting material is at least one selected from the group consisting of silica, alumina, glass, mica, and resin.
[0015] [3] The coated pigment according to [1] or [2], wherein the substrate is a metal sheet coated with the light-transmitting material.
[0016] [4] The coated pigment according to [3], wherein the metal flakes are at least one selected from the group consisting of aluminum, copper, nickel, tin, titanium, zinc, alloys containing any one or more of these, and stainless steel.
[0017] [5] The coated pigment according to any one of [1] to [4], wherein a protective layer composed of any one of metal oxides, metal hydroxides, metal oxide hydrates, resins, or a combination thereof is provided on the magnetite layer.
[0018] [6] A resin composition comprising the coated pigment according to any one of [1] to [5].
[0019] [7] A coated article obtained by coating the resin composition described in [6] on a substrate.
[0020] [8] A cosmetic comprising the coated pigment according to any one of [1] to [5].
[0021] The coated pigment of the present invention can have high chroma and color rendering properties, and can express interference colors of various colors such as red, blue, yellow to green. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 These are photographs of the coated pigments obtained in Example 12 and Comparative Example 6 applied to a sheet and formed into a cylindrical shape.
[0023] Figure 2 These are photographs of the coated pigments obtained in Example 11 and Comparative Example 5 applied to a sheet and formed into a cylindrical shape.
[0024] Figure 3 These are photographs of the coated pigments obtained in Example 4 and Comparative Example 1 applied to a sheet and formed into a cylindrical shape.
[0025] Figure 4 These are photographs of the coated pigments obtained in Example 10 and Comparative Example 4 applied to a sheet and formed into a cylindrical shape. DETAILED DESCRIPTION
[0026] Hereinafter, embodiments of the present invention will be described in detail.
[0027] The present invention relates to a coated pigment having interference color, comprising a substrate at least the surface of which is made of a light-transmitting material and a magnetite layer coating the substrate.
[0028] [Base material]
[0029] The substrate of the present invention is a material that becomes the core of the coated pigment of the present invention, and at least the surface is composed of a translucent material. As long as at least the surface is composed of a translucent material, the substrate as a whole may be the translucent material, or may be a material formed by coating a core material composed of another material with the translucent material.
[0030] The volume average particle size (D 50 ) can be arbitrarily selected within the range of the particle size of the coated pigment of the present invention described later, and is more preferably 0.5 μm to 200 μm or less. If it is 0.5 μm to 200 μm, it is preferred from the viewpoint of being well coated with the above-mentioned magnetite layer. When it is less than 0.5 μm, the specific surface area of the substrate becomes large, so it is difficult to fully deposit the magnetite layer. On the other hand, when it is greater than 200 μm, the specific surface area is small, the contact probability between the substrate and the coated magnetite particles is reduced, and it is difficult to use the magnetite layer for good coating.
[0031] The substrate may be in a particle or flake shape, and is preferably in a flake shape.
[0032] As the above-mentioned substrate, in the case of a translucent substrate consisting only of a translucent material, as the translucent substrate, a known substrate can be used without particular limitation. Among them, the translucent substrate consisting of silicon dioxide, aluminum oxide, glass, mica and resin, and their composites have high light transmittance and are preferably used.
[0033] Furthermore, since the light-transmitting substrate itself serves as an interference layer, it is preferred that the thickness of the substrate be uniform if it is in the form of particles or flakes.
[0034] In addition, as the above-mentioned substrate, the surface of the core material is coated with a translucent material. When the core material and the translucent material are composed of different materials, the material of the core material is not particularly limited, and can be a translucent material different from the translucent material constituting the surface, or can be an opaque material. Examples of the opaque material include metals, plate-like iron oxides, etc. As the metal, there is no particular limitation, and known metals can be used, but examples include aluminum, copper, nickel, tin, titanium, zinc, alloys containing at least one of them, and stainless steel, etc.
[0035] As the light-transmitting material, as described above, the same materials as those used as the light-transmitting base material composed only of the light-transmitting material as the base material can be cited.
[0036] As the core material, if metal flakes are used, a pigment having particularly high brightness and chroma can be obtained, so it is preferred. In particular, if flakes made of aluminum or aluminum alloy among the above metals are used as the metal flakes, it is inexpensive and has high brightness, so it is preferred.
[0037] In addition, at this time, the coating layer composed of the translucent material coated on the core material becomes an interference layer that determines the color tone, so its thickness is preferably uniform. When the translucent layer is thicker than 100nm, the interference color becomes stronger, and a coated pigment with high chroma can be obtained. Furthermore, as the thickness increases, the color tone change (color difference characteristics) according to the observation angle becomes stronger.
[0038] [Magnetite layer]
[0039] The magnetite layer of the present invention is a layer composed of magnetite coating the above-mentioned substrate. As the magnetite layer coating the above-mentioned substrate, if a magnetite layer having a specific lattice constant is used, a coated pigment having higher chroma and color rendering can be obtained. In addition, by changing the conditions of each component constituting the coated pigment, interference colors of various colors such as red, blue, yellow to green can be expressed. Therefore, a coated pigment having interference colors of various colors can be obtained.
[0040] This is believed to be due to the loss of oxygen atoms from magnetite, which results in oxygen deficiency, thus changing the crystal structure. As a result, the refraction and transmission of light in the magnetite layer change, and the chromaticity and color rendering tend to increase in depth and intensity. In addition, it is possible to express interference colors of multiple colors as described above.
[0041] The lattice constant of the magnetite layer above needs to be Above, preferably If the lattice constant is less than There is a risk that the chroma of the interference color will decrease, and sufficient color rendering may not be obtained.
[0042] The upper limit of the lattice constant of the magnetite layer is not particularly limited, but may be The following are preferably Below. Can exceed But it is not easy to obtain The lattice constant of the magnetite layer increases as the oxygen atoms decrease too much and the risk of becoming non-magnetite increases.
[0043] The average thickness of the magnetite layer is not particularly limited, but is preferably 10 nm to 200 nm, more preferably 20 nm to 120 nm. Within this range, the chroma of the interference color is particularly good.
[0044] [Thickness of the light-transmitting layer and magnetite layer of the substrate]
[0045] When a substrate in which a core material is coated with a light-transmitting material on its surface is used as the substrate, the hue of the interference color also changes depending on the thickness of the magnetite layer.
[0046] For example, when an aluminum sheet (metal substrate) having a translucent layer of about 140 nm made of silicon dioxide is used as a substrate, if a layer of about 30 nm thick made of magnetite is coated on the substrate, a pink-colored coated pigment (metallic pigment) with high chroma having magnetism can be obtained, and if a layer of about 100 nm thick made of magnetite is coated on the substrate, a coated pigment (metallic pigment) that changes from green to purple depending on the angle of observation can be obtained. It is speculated that this is because when the magnetite layer becomes thicker, a difference in optical path length also occurs between the reflected light on the surface of the magnetite layer and the reflected light at the interface between the magnetite layer and the translucent layer.
[0047] [Protective layer]
[0048] The coated pigment of the present invention may further be provided with a protective layer on the surface of the magnetite layer as required.
[0049] The material of the protective layer is not particularly limited as long as it is transparent and does not impair the coloration of the coated pigment. As such a protective layer, metal oxides, metal hydroxides, metal oxide hydrates, resins and their composites can be cited, and they can be appropriately selected from them according to the purpose.
[0050] For example, if the protective layer is a metal oxide, water resistance can be improved. In addition, if the protective layer is a resin, the adhesion and chemical resistance of the coating film containing the coated pigment of the present invention are improved.
[0051] As a method for forming the protective layer, any known method can be used as long as it is a method for coating the pigment. For example, a resin coating layer can be formed by free radical polymerization in a slurry, and a metal oxide layer can be formed by a sol-gel method. It should be noted that the protective layer can be formed before or after the magnetite layer is fired.
[0052] [Manufacturing of coated pigments]
[0053] The coated pigment of the present invention can be produced by the following method.
[0054] First, the substrate can be produced by the following method: When a light-transmitting substrate composed of only a light-transmitting material is used as the substrate, the material can be adjusted to a predetermined size and thickness and then used as the substrate as it is.
[0055] In addition, when a material formed by coating a translucent material on the surface of a core material is used as a substrate, a slurry of the core material based on alcohol or the like is prepared, and an alcohol solution of a component of a raw material of the translucent material is dripped thereto to form a coating layer of the translucent material on the surface of the core material. Then, by performing solid-liquid separation and drying, a substrate in which the surface of the core material is coated with the translucent material can be obtained.
[0056] Next, as a method of forming a magnetite layer on the surface of a substrate, the following method can be mentioned.
[0057] First, the substrate is dispersed in water to obtain a slurry. Then, while stirring the slurry in a deoxygenated sealed container, a Fe-containing 2+ At this time, due to the pH change, the pH is maintained between 6.5 and 14 by a pH adjuster, and an oxidant is used to maintain the redox potential of the slurry between about -160mV and -750mV. Thus, a magnetite layer can be coated on the substrate. The pH range is preferably maintained between 6.5 and 11.0, and an oxidant is preferably used to maintain the redox potential of the slurry between about -300mV and -500mV.
[0058] [Coating pigment]
[0059] The particle size of the coated pigment of the present invention produced in this way is not particularly limited, and it depends on the application, but is generally 1.5 to 2.0 volume average particle size (D 50 If the particle size is smaller than 0.5 μm, more light will be reflected from the particle surface, making it difficult to develop interference colors with high chroma.
[0060] For example, when used for coating, if the particle size is 0.5 μm to 50 μm, the protrusion of coarse particles on the surface of the coating film can be eliminated, and the coating can be smoothly performed.
[0061] When the coated pigment is used for printing, for example, in screen printing or gravure printing, a particle size of about 20 μm or less is preferred in order to prevent clogging of the plate and ensure concealment.
[0062] Furthermore, a larger size can be selected for cosmetics and resin injection molded products, and by using a coated pigment of 50 μm or more, a grainy design with a gloss derived from the base material can be obtained.
[0063] The particle shape of the coated pigment is not particularly limited, but a flake shape is preferred because the brightness, chroma, and color transition properties (color-shifting properties) are enhanced due to orientation.
[0064] [Firing process]
[0065] In the present invention, after forming the magnetite layer, firing is performed in an inert gas atmosphere, a reducing gas atmosphere, or a reduced pressure (or vacuum) of 50 kPa or less, thereby converting the magnetite layer into an oxygen-deficient layer with a lattice constant within a predetermined range.
[0066] The inert gas is not particularly limited, but examples thereof include nitrogen gas, argon gas, etc. The reducing gas is not particularly limited, but examples thereof include hydrogen gas, natural gas, city gas, etc.
[0067] The reducing gas atmosphere also includes a case where a reducing gas and an inert gas are mixed and used.
[0068] If the firing process is carried out in an oxygen atmosphere without using such an inert gas or reducing gas, it tends to be difficult to obtain high chroma and to express interference colors. Even if interference colors are expressed, it tends to be difficult to express interference colors with sufficiently significant differences.
[0069] The firing temperature is preferably 300° C. or higher, more preferably 300° C. to 800° C. If the firing temperature is lower than 300° C., oxygen defects are not generated and the predetermined lattice constant cannot be achieved. Therefore, it tends to be difficult to obtain high chroma and to express interference colors. Even when expressing interference colors, it tends to be difficult to express interference colors with sufficiently significant differences.
[0070] On the other hand, when the firing temperature exceeds 800°C, the particle size increases due to the aggregation of the coated iron oxide particles, and the coated pigments aggregate due to the aggregation of the iron oxide particles on the surface, so that good color development cannot be obtained. Furthermore, the film interface peels off due to the melting and thermal expansion of the substrate itself, resulting in reduced durability.
[0071] The firing time is preferably 5 minutes to 24 hours from the time when the temperature reaches 300°C or higher, and more preferably 30 minutes to 3 hours. If it is less than 5 minutes, sufficient oxygen defects are not generated and the predetermined lattice constant cannot be achieved. If it exceeds 3 hours, the productivity decreases, which is not preferred. In addition, even if the firing is performed for more than 24 hours, there is almost no change in the lattice constant beyond that, which leads to agglomeration and damage to the coated pigment, which is not preferred.
[0072] [use]
[0073] The coated pigment of the present invention can be used as a resin composition having bright interference color by mixing with a resin. Furthermore, by applying the coated pigment to sheets such as paper and resin sheets, various movable and immovable properties, a coated article having interference color can be obtained.
[0074] Furthermore, by mixing the coated pigment of the present invention with various cosmetics, it is possible to obtain a coated pigment-containing cosmetic having an interference color.
[0075] [Effects of the invention]
[0076] In the present invention, by setting the above-mentioned conditions, especially the lattice constant of the magnetite layer, within a specific range, and combining with other conditions as needed, the above-mentioned inventive effect can be obtained, that is, having high chroma and color rendering, and producing various interference colors such as red, blue, yellow to green, thereby being able to express interference colors of multiple colors.
[0077] As conditions for setting the lattice constant of the above-mentioned magnetite layer within a specific range and the above-mentioned other conditions, there can be cited the thickness of the magnetite layer, the type of material of the substrate layer, the thickness of the translucent material of the substrate layer, firing conditions (firing temperature, firing time, firing environment), etc.
[0078] Example
[0079] The present invention will be described below using examples. First, the test methods and raw materials used in the examples are as follows.
[0080] (Test method)
[0081] [Lattice constant]
[0082] The coated pigment was uniformly filled into the measurement cell, and the magnetite layer of the coated pigment was determined by an X-ray diffraction device (trade name: "Smart Lab" manufactured by Rigaku Co., Ltd.). The measurement conditions used CuKα rays as the X-ray source, with a tube voltage of 40 kV, a tube current of 30 mA, a sampling width of 0.01°, and a scanning speed of 0.2° / min. Using this result, the "precision of lattice constants" of the comprehensive powder X-ray analysis software PDXL2 was performed to calculate the lattice constant of magnetite.
[0083] [tone]
[0084] 16.0 g of an acrylic resin binder (NIPPE ACRYL Auto Clear, manufactured by Nippon Paint Co., Ltd.) was added to 4.0 g of the coated pigment, and the mixture was uniformly mixed using a planetary stirring degassing machine (MAZERUSTAR KK-400W, manufactured by Kurabo Industries Ltd.) to prepare a coating material.
[0085] This was applied onto coated paper using an applicator having a gap of 100 μm, and naturally dried at room temperature to prepare a coating film for evaluation.
[0086] The color tone was evaluated using an X-Rite MA68II multi-angle spectrophotometer. The colorimetric value was expressed in the L*a*b* colorimetric system (CIE1976), and the colorimetric detection was performed on light that was 15° offset from regular reflection relative to the incident light.
[0087] At this time, L* represents lightness, color a* represents chromaticity representing hue and chroma on the red-green axis, b* represents chromaticity representing hue and chroma on the yellow-blue axis, and ΔE represents the color difference (the distance between two points on the L*a*b* color space) between the embodiment in which the firing process is performed and the comparative example in which the firing process is performed under the same conditions except that the firing process is not performed.
[0088] [magnetic]
[0089] 1.0 g of the coated pigment was placed in a 50 cc glass beaker, and 10 g of ion exchange water was added to prepare a slurry. Next, a ferrite magnet (φ20 mm, thickness 5 mm, surface magnetic flux density 100 mT) was placed outside the bottom of the beaker to visually check for magnetism.
[0090] In addition, when the coated pigment does not have magnetism, the slurry does not change, but when the coated pigment has magnetism, the coated pigment is oriented or gathered on the magnet itself due to magnetism, so the magnetism can be visually confirmed.
[0091] (raw materials)
[0092] [Base material]
[0093] ·Flake aluminum pigment…Made by Toyo Aluminum Co., Ltd. Trade name: 5422NS
[0094] ·IPA…Isopropyl alcohol, manufactured by Godo Co., Ltd. ·30% hydrogen peroxide solution…manufactured by FUJIFILM Wako PureChemical Corporation
[0095] · Ammonia water… FUJIFILM Wako Pure Chemical Corporation: 25% by mass
[0096] ・Tetraethoxysilane…Made by FUJIFILM Wako Pure Chemical Corporation
[0097] [Magnetite layer]
[0098] · Polyacrylic acid…Made by Toagosei Co., Ltd. Trade name: Aron T-50
[0099] ·Sodium acetate…manufactured by Niwa Gosei Co., Ltd.
[0100] · Ferrous sulfate heptahydrate…Made by Ensho Industry Co., Ltd.
[0101] ·Sodium hydroxide…Made by FUJIFILM Wako Pure Chemical Corporation
[0102] <Example 1>
[0103] (Base material manufacturing process)
[0104] The substrate used is a substrate having a translucent layer composed of silica formed on the surface of a commercially available flaky aluminum pigment. First, 150 g of flaky aluminum pigment in terms of solid content is put into 1000 g of IPA, and stirred and mixed at 75°C to obtain a slurry. After stirring 30% hydrogen peroxide water for 30 minutes, ammonia water and 100 g of ion exchange water are added to adjust the pH value of the slurry to 10.0. A solution obtained by dissolving 300 g of tetraethoxysilane in 300 g of IPA is slowly added dropwise, and further stirred and mixed at 75°C for 4 hours. Then, the slurry is separated into solid and liquid, and dried in an oven at 150°C for 24 hours, thereby obtaining a flaky aluminum substrate having a translucent layer composed of silica formed on the surface.
[0105] (Magnetite layer manufacturing process)
[0106] In a closed reactor equipped with a stirrer, a pH measuring electrode, and a gas introduction tube, 120 g of the substrate obtained above and 1000 g of ion-exchanged water sufficiently degassed with nitrogen were added to obtain a slurry in which the substrate was dispersed in the ion-exchanged water.
[0107] Next, 1.0 g of polyacrylic acid and 7 g of sodium acetate were added to the above slurry, and the slurry was heated until it reached 40° C. while being stirred.
[0108] Next, an aqueous solution was prepared by dissolving 110 g of ferrous sulfate heptahydrate in 300 g of ion exchange water fully degassed with nitrogen, and the aqueous solution of ferrous sulfate was slowly added to the stirred slurry over 1 hour. At this time, a 5 wt % aqueous sodium hydroxide solution was added to adjust the pH to 9. In addition, air was introduced into the reactor to adjust the redox potential to -400 mV.
[0109] Thereafter, the mixture was filtered and washed with water, and then washed with IPA and dried in an oven at 160° C. for 6 hours to obtain a magnetite-coated pigment.
[0110] (Firing process)
[0111] By firing 200 g of the magnetite-coated pigment obtained above at 300° C. for 2 hours under argon, an interference color pigment having a lattice constant of magnetite within a specified range, bright pink in the center, and red as it moves toward the ends is obtained. The measurement results of the color tone, magnetic properties, and lattice constant of the obtained interference color pigment are shown in Table 1.
[0112] <Examples 2 to 12, Comparative Examples 2 to 3>
[0113] An interference color pigment was obtained by the method described in Example 1 except for the conditions of each step shown in Table 1. Table 1 shows the measurement results of the color tone, magnetic properties and lattice constant of the obtained interference color pigment.
[0114] <Comparative Examples 1, 4 to 6>
[0115] The coated pigment was prepared in the same manner as in Example 1 except that the conditions of the substrate production step and the magnetite production step shown in Table 1 were followed and the firing step was not performed. Table 1 shows the measurement results of the color tone, magnetic properties, and lattice constant of the obtained interference color pigment.
[0116] [Table 1]
[0117]
[0118] Note: *1 Color difference compared with Comparative Example 1
[0119] *2 Color difference compared with Comparative Example 4
[0120] *3 Color difference compared with Comparative Example 5
[0121] *4 Color difference compared with Comparative Example 6
[0122] *5 Vacuum refers to a reduced pressure state of 1 kPas.
[0123] In the table, “-” means that the color tone was not measured and that the photograph was not shown in the figure.
[0124] According to the above results, in Examples 1 to 12 that satisfy the invention requirements of the present application, dark interference colors with higher chroma are obtained, while in Comparative Examples 1 to 6 that do not satisfy the invention requirements of the present application, only light colors with low chroma are sometimes obtained, and no interference colors are generated.
[0125] In addition, since each of the Examples and Comparative Examples has magnetism, it is understood that the magnetite layer maintains the structure of magnetite.
[0126] from Figure 1 to Figure 4 This can also be seen. Figure 1 to Figure 4 The sheet coated with the interference color pigment obtained in each example and comparative example is wound into a cylindrical shape and placed so that the circumferential surface is in contact with a worktable (arranged so that the circumferential direction is the up-down direction of each figure). Due to this arrangement, the color tone when observed at an angle almost perpendicular to the cylindrical surface can be observed in the center, and as it moves in the up-down direction, the color tone when observed in a state where the angle with the cylindrical surface becomes smaller can be observed, so the presence or absence of interference color can be confirmed.
[0127] Figure 1Example 12 (right) and Comparative Example 6 (left) differ in the presence or absence of a firing process, and have a difference in whether the lattice constant meets the specified range. In Example 12, bright yellow (central part) to bright green (upper and lower parts), high chroma, and clear interference colors are obtained for the change of color tone, while in Comparative Example 6, light yellow, the chroma is not too high, and the change of color tone between the central part and the upper and lower parts is difficult to see, and no clear interference color can be obtained.
[0128] Figure 2 Example 11 (right) and Comparative Example 5 (left) differ in the presence or absence of a firing process, and have a difference in whether the lattice constant meets the specified range. In Example 11, the central part is bright orange, and as it moves to the upper and lower parts, it changes from bright yellow to bright green, and the chroma is high, and clear interference colors are obtained for the change in hue. In Comparative Example 5, the chroma is not too high, and although there is a change in hue between the central part and the upper and lower parts, it is difficult to say that it is clear, and it is difficult to say that clear interference colors are obtained.
[0129] Figure 3 Example 4 (right) and Comparative Example 1 (left) differ in the presence or absence of a firing process, and have a difference in whether the lattice constant meets the specified range. In Example 4, the central part is bright red, and as it moves upward and downward, it changes from bright orange to bright green, and the chroma is high, and a clear interference color is obtained for the change in hue. In Comparative Example 1, the central part is light pink, and as it moves upward and downward, it changes to light yellow, but the chroma is not too high. Although there is a change in hue between the central part and the upper and lower parts, it is difficult to say that it is clear, and it is difficult to say that a clear interference color is obtained.
[0130] Figure 4 The conditions of the firing process of Example 10 (right) and Comparative Example 4 (left) are different, and there is a difference in whether the lattice constant meets the specified range. In Example 10, the central part is bright blue, and as it moves upward and downward, it changes to bright reddish purple, and the chroma is high, and clear interference colors are obtained for the change of color tone, while in Comparative Example 4, the whole is silver, and no interference color can be confirmed.
Claims
1. A coated pigment comprising a substrate at least the surface of which is made of a light-transmitting material and a magnetite layer covering the substrate, The lattice constant of the magnetite layer is above, The substrate is a metal sheet coated with the light-transmitting material.
2. The coated pigment according to claim 1, in, The light-transmitting material is at least one selected from the group consisting of silica, alumina, glass, mica and resin.
3. The coated pigment according to claim 1, in, The metal thin sheet is at least one selected from aluminum, copper, nickel, tin, titanium, zinc, alloys containing any one or more of these, and stainless steel.
4. The coated pigment according to any one of claims 1 to 3, in, A protective layer composed of any one of metal oxide, metal hydroxide, metal oxide hydrate, resin or a combination thereof is provided on the magnetite layer. 5 . A resin composition comprising the coated pigment according to claim 1 .
6. A coated article obtained by coating the resin composition according to claim 5 on a substrate.
7. A cosmetic comprising the coated pigment according to any one of claims 1 to 4.
Citation Information
Patent Citations
High-chroma orange-colored pearl pigment
JP1998259318A
Magnetic pearlescent pigment and preparation method thereof
CN101445674A
Magnetic Pigments Comprising A Flaky Substrate And A Layer Of Maghemite
CN102803400A
Magnetic pigments
CN103249783A
Black bright pigment, and cosmetic, coating composition, resin composition and ink composition comprising the same
CN1856550A
